Navigating Through Change: Uncovering the Challenges of Agile Coaching in Indian IT Companies - Nellore, Sravana Kumar (Digital Repository of Theses, 2025)
This research explores the key challenges faced by Agile coaches in Indian IT companies during Agile transformation. As Agile practices become more widespread, the role of coaching has grown in importance—yet many organisations continue to face difficulties that impact the success of Agile implementation. The study is based on quantitative data collected through a structured survey, with 203 valid responses from Agile Coaches and Scrum Masters across various Indian IT firms. Using descriptive statistics, correlation, regression analysis, ANOVA, and one-sample t-tests, the research examines how factors such as organisational culture, Agile maturity, and remote working influence Agile coaching outcomes. The findings reveal that cultural barriers, lack of clarity in roles, leadership misalignment, and communication issues in remote environments are among the most significant challenges for Agile coaches. These obstacles consistently emerged across participants, indicating shared pain points within the industry. While the research does not focus on offering solutions, it draws attention to areas where Agile coaching is most impacted. By doing so, it adds to the broader understanding of Agile adoption in India’s IT sector and provides a basis for future research focused on addressing these systemic challenges.